2003
DOI: 10.1089/109493103769710497
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Presence during VR Immersion: A Comparative Study of the Reactions of Phobic and Non-phobic Participants in Therapeutic Virtual Environments Derived from Computer Games

Abstract: Virtual reality can be used to provide phobic clients with therapeutic exposure to phobogenic stimuli. However, purpose-built therapeutic VR hardware and software can be expensive and difficult to adapt to individual client needs. In this study, inexpensive and readily adaptable PC computer games were used to provide exposure therapy to 13 phobic participants and 13 non-phobic control participants. It was found that anxiety could be induced in phobic participants by exposing them to phobogenic stimuli in thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
121
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(138 citation statements)
references
References 18 publications
13
121
2
2
Order By: Relevance
“…Those with the lowest presence scores were also the ones reporting less discomfort when they encountered the first virtual dog (see Figure 4B). These observations confirm the consistency of our measurements, underlying the potential link between emotion and presence (Robillard, Bouchard, Fournier, & Renaud, 2003). The different dogs evoked different reactions (see Table 3), mainly idiosyncratic (Friedman test (10, 3) = 10.06, p = 0.02, Kendall's coefficient of concordance W = .33).…”
Section: Resultssupporting
confidence: 86%
“…Those with the lowest presence scores were also the ones reporting less discomfort when they encountered the first virtual dog (see Figure 4B). These observations confirm the consistency of our measurements, underlying the potential link between emotion and presence (Robillard, Bouchard, Fournier, & Renaud, 2003). The different dogs evoked different reactions (see Table 3), mainly idiosyncratic (Friedman test (10, 3) = 10.06, p = 0.02, Kendall's coefficient of concordance W = .33).…”
Section: Resultssupporting
confidence: 86%
“…Virtual environments developed with the Unreal Engine include systems for acrophobia and claustrophobia therapy [RBFR03] …”
Section: Unreal Enginementioning
confidence: 99%
“…Building realistic virtual environments is a complex, expensive and time consuming process [Lai02, RBFR03,SD00,SH01]. Lepuras and Vassilakis [LV05] note that state-of-the-art virtual environments are both costly to build and to maintain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robillard et al (2003) reported a significant correlation (r = .74, < p .001) between anxiety and the feeling of presence. To assess the direction of the relationship between anxiety and presence, Bouchard, St-Jacques, Robillard and Renaud (2008) manipulated anxiety while participants suffering from a phobia of snakes were immersed in virtual reality, then evaluated the impact of anxiety on the feeling of presence.…”
mentioning
confidence: 93%